Lucinda's secret - DiTerlizzi, Tony.; Black, Holly (New York : Simon & Schuster Books for Young Readers, 2003)
With goblins, trolls, and the house boggart all trying to get them, the Grace children turn to Great Aunt Lucinda for help.
In which many things are turned inside out -- In which many people are mad -- In which stories are told and a theft is discovered -- In which the grace children look for a friend -- In which there are many riddles and few answers -- In which Jared fulfills the Phooka's prediction -- In which Jared is finally pleased to have a twin.
Sequel to: The seeing stone.
Keywords: Brothers and sisters -- Fiction; Great-aunts -- Fiction; Supernatural -- Fiction; Siblings -- Juvenile fiction; Great-aunts -- Juvenile fiction; Supernatural -- Juvenile fiction